Pengaruh Good Governance dan Pengendalian Internal Terhadap Kinerja Keuangan Desa di Desa Batu Putih Kecamatan Mallawa Kabupaten Maros - Khaeril, Khaeril; Ruslan, Ruslan; Lomban, Marcelina (Insan Cita Bongaya Research Journal, 2025)
Abstract : The Influence of Good Governance and Internal Control on Village Financial Performance in Batu Putih Village, Mallawa District, Maros Regency. Marcelina Lomban. Et.al ( 2024 ) This study aims to identify the Influence of Good Governance and Internal Control on Village Financial Performance in Batu Putih Village, Mallawa District, Maros Regency. The type of data used in this study is primary data obtained through questionnaire filling. The respondents were Village Officials, BPD, Hamlet Heads, State Apparatus, Village Youth and Village Communities in Batu Putih Village, Mallawa District, Maros Regency. The total number of respondents was 45 people. This study uses a type of quantitative research with a descriptive approach. The data collection method uses a questionnaire with a Likert scale. The data that has been collected is processed and analyzed through the SPSS application using instrument tests, tests, classical assumption tests, normality tests, multicollinearity tests, heteroscedasticity tests, multiple linear regression tests, and hypothesis tests and then an interpretation is made for the research results. The results of the study show that good governance has a positive and insignificant effect on village financial performance, while Internal Control has a significant positive effect on village financial performance and the influence of Good Governance and Internal Control simultaneously affects village financial performance. The results of this study show that the implementation of Good Governance has not had a significant impact partially, the strengthening of Internal Control has consistently supported the improvement of village financial performance. Overall, between these two factors, it is necessary to continue to improve to optimize village financial performance. Keyword : Good Governance, Internal Control, Financial Performance